Long Run Risks, the Macroeconomy, and Asset Prices - Bansal, Ravi; Kiku, Dana; Yaron, Amir (American Economic Review, 2010)
Long-Run Risk (LRR) model which emphasizes the role of long-run risks, that is, low-frequency movements in consumption growth rates and volatility, in accounting for a wide-range of asset pricing puzzles. In this article we present a generalized LRR model, which allows us to study the role of cyclical fluctuations and macroeconomic-crisis on asset prices and expected returns. The Bansal and Yaron (2004) LRR model contains (i) a persistent expected consumption growth component, (ii) long-run variation in consumption volatility, and (iii) preference for early resolution of uncertainty. To evaluate the role of cyclical risks, we incorporate a cyclical component in consumption growth — this component is stationary in levels. To study financial market crisis, we also entertain jumps in consumption growth and consumptionvolatility. We find that the magnitude of risk compensation for cyclical risks in consumption critically depends on the magnitude of the inter-temporal elasticity of substitution (IES). When the IES is larger than one, cyclical risks carry a very small risk-premium and the compensation for long-run risks is large. When IES is close to zero, the risk compensation for cyclical risks is large, however, in this case the risk-free rate is implausibly high (in excess of 10 percent). Given this, it seems unlikely that the compensation for cyclical risk is of economically significant magnitude. This implication is also consistent with Robert E. Jr. Lucas (1987), who argues that economic costs of transient shocks are small and those for trend shocks are large. Moreover, Ravi Bansal, Robert F. Dittmar and Dana Kiku (2009) provide evidence from equity markets that the compensation for long-run risks is large and that for cyclical risk is quite small.